Second screening for news: Effects of presentation on information processing and program liking. (July 2018) - Schaap, Gabi; Kleemans, Mariska; Van Cauwenberge, Anna
Abstract: This study investigated the effects of second screen presentation mode on information processing and program liking. In an experiment, 121 participants watched a television news program. One group was assigned to a dual screen condition in which participants were required to actively look up additional information on a second screen ('look-up condition'), while a second group were assigned to a dual screen condition in which participants were directly presented with the additional information on the second screen, with no looking-up required ('presented information condition'). In a third condition, the single-screen condition, participants merely watched the news program. Results show that second screening negatively impacts factual recognition and program liking, regardless of presentation mode. While cued recall of information was lower in the second screen conditions than in the single screen condition, participants in the condition with presented information scored significantly higher on cued recall compared to the look-up condition. Analyses show the effects can be explained by the different levels of cognitive load elicited by different presentation modes. Highlights: News recall and recognition suffer when using a second screen while watching the news. News program liking decreases when second screening. A 'simpler' second screen format decreases the negative effect only for cued recall, not for recognition and liking. The effects can be explained by the increased cognitive load elicited by using a second screen.